Estudo dos metabólitos secundários de Condalia buxifolia e Scutia buxifolia e suas atividades antimicrobianas - Maldaner, Graciela (2005)
The present work describes the study of the secondary metabolites of two species that belong to the Rhamnaceae family: Condalia buxifolia and Scutia buxifolia, and the study of the ratio structure/activity of seven cyclopeptidcs alkaloids and one neutral cyclopeptidc: scutianine-B (24), scutianine-C (14), scutianine-D (15), scutianine-E (16), scutianine-F (18), scutianine-M (37), condaline-A (22) and scutianene-D (38). In the bark of the bole of Condalia buxifolia three metabolites were isolated: lupeol (34), taraxerol (35) and β-sitosterol (33). In the bark of the roots was isolated the cyclopeptidc alkaloid condaline-A (22). In the bark of the roots of Scutia buxifolia the metabolites ursolic acid (36) and β-sitosterol (33) were isolated, whereas the cyclopeptidcs alkaloids scutianine-B (24), scutianine-C (14) and scutianine-D (15) were only identified in this part of the plant by comparison with authentic samples. Additionally, the antimicrobial activity of the portions and the isolated metabolites of Condalia buxifolia and Scutia buxifolia were analyzed by Bioautography test, utilizing different microorganisms: two gram positive bacteria (Staphylococcus aureus (Sa) and Staphylococcus epidermidis (Se)), three gram negative bacteria (Klebsiella pneumonia (Kp), Salmonella setúbal (Ss) and Escherichia coli (Ec)) and two fungus (Saccharomyces cerevisiae (Sc) and Candida albicans (Ca)). In this analysis it was observed that the stereochemistry of the amino acids that compose the alkaloids structure and the presence of the basic group of these structures are important to this sort of activity.